Progression of pulmonary arterial hypertension: A study in model - Agus Cahyono; Irwanto Irwanto; Mahrus A. Rahman; Widjiati Widjiati (Open Veterinary Journal)
Background: Pathobiology of pulmonary arterial hypertension (PAH) is complex. Patology and molecular biology signature during its progression is interesting to study.